2012
DOI: 10.1159/000345299
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Mapping of H1 Histone and Ribosomal RNA Genes in Hybrids between Catfish Species <b><i>Pseudoplatystoma corruscans</i></b> and <b><i>Pseudoplatystoma reticulatum</i></b>

Abstract: A physical chromosome mapping of the H1 histone and 5S and 18S ribosomal RNA (rRNA) genes was performed in interspecific hybrids of Pseudoplatystoma corruscans and P. reticulatum. The results showed that 5S rRNA clusters were located in the terminal region of 2 chromosomes. H1 histone and 18S ribosomal genes were co-localized in the terminal portion of 2 chromosomes (distinct from the chromosomes bearing 5S clusters). These results represent the first report of association between H1 histone and 18S genes in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 49 publications
(29 reference statements)
3
8
1
Order By: Relevance
“…Few data reporting the chromosomal location of the histone genes in fishes are available [Pendás et al, 1994b;Hashimoto et al, 2011Hashimoto et al, , 2012Lima-Filho et al, 2012;Pansonato-Alves et al, 2013]. In the present study, the H1 and H3 histone clusters are colocalized and conserved in the same chromosome pair in both karyomorphs, corroborating previous data for the genus Astyanax [Hashimoto et al, 2011;Silva et al, 2013] and reinforcing the conserved distribution pattern of these sequences.…”
Section: Discussionsupporting
confidence: 91%
“…Few data reporting the chromosomal location of the histone genes in fishes are available [Pendás et al, 1994b;Hashimoto et al, 2011Hashimoto et al, , 2012Lima-Filho et al, 2012;Pansonato-Alves et al, 2013]. In the present study, the H1 and H3 histone clusters are colocalized and conserved in the same chromosome pair in both karyomorphs, corroborating previous data for the genus Astyanax [Hashimoto et al, 2011;Silva et al, 2013] and reinforcing the conserved distribution pattern of these sequences.…”
Section: Discussionsupporting
confidence: 91%
“…Despite the restricted sampling, these studies revealed some particular characteristics, such as differential dispersion of sites and association with 5S or 18S rDNA (Hashimoto et al , 2011, 2013; Lima-Filho et al , 2012; Pansonato-Alves et al , 2013a, 2013b). More recent studies also showed that H1, H3 and H4 histone genes are clustered at the same site in fishes of genus Astyanax (Pansonato-Alves et al , 2013b; Silva et al , 2013).…”
Section: Discussionmentioning
confidence: 97%
“…In fish species, data about chromosomal location of histone sequences are restricted to eight species mapped for H1 genes (Pendás et al , 1994; Hashimoto et al , 2011, 2013; Lima-Filho et al , 2012) and only five species with mapped H3 sites (Pansonato-Alves et al , 2013a, 2013b; Silva et al , 2013), all of them presenting histone sequences as conspicuous blocks in chromosomes. Despite the restricted sampling, these studies revealed some particular characteristics, such as differential dispersion of sites and association with 5S or 18S rDNA (Hashimoto et al , 2011, 2013; Lima-Filho et al , 2012; Pansonato-Alves et al , 2013a, 2013b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PDU and PPO were characterized by a small and stable number of ribosomal DNA (rDNA) clusters, contrasting with the polymorphisms observed in AOL . Still, there are few studies using in-depth molecular cytogenetic analyses on natural fish hybrids (Fujiwara et al, 1997;Zhu et al, 2006;Gromicho et al, 2006b;Hashimoto et al, 2012;Rampin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%